EXPLORATION OF MOTHER POST SECTIO CAESAR WITH ACUTE PAIN: CASE REPORT - Sri Wahyuningsih; Nurul Hayati; Rizeki Dwi Fibriansari; Siti Anisa; Emi Suprapti (Indonesian Journal of Health Care Management, 2022)
Actions after sectio caesarea surgery can provide problems that arise as a result of the incision of tissue tears on the abdominal wall and uterine wall causing continuity changes so that the patient feels pain. One of the non-pharmacological therapies that can be given to postoperative sectio caesarea patients is gradual mobilization in overcoming pain nursing problems with the aim of reducing pain and restoring the patient's condition. The purpose of this study was to explore nursing care for post sectio caesarea mothers with acute pain nursing problems in the Teratai Room RSUD dr. Haryoto Lumajang. Descriptive qualitative research method through case reports on postpartum patients with suture wounds on the abdominal wall in the Lotus Room RSUD dr. Haryoto Lumajang. Nursing care for 3 days started from data collection with interview techniques, observation, physical examination, and documentation. The results obtained Mrs. S P20002 postpartum cesarean delivery patient with indication of breech location with acute pain in abdominal wall suture wound in April 2021. Management according to intervention by gradually mobilizing, deep breathing relaxation therapy and collaborating with the medical team. The conclusion of the acute pain problem in the suture wound on the abdominal wall was felt to be reduced by the patient, on the 2nd and 3rd day after comprehensive nursing care was carried out.